2007
DOI: 10.1016/j.pain.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Body perception disturbance: A contribution to pain in complex regional pain syndrome (CRPS)

Abstract: 12 Abstract 13In spite of pain in the CRPS limb, clinical observations show patients pay little attention to, and fail to care for, their affected 14 limb as if it were not part of their body. Literature describes this phenomenon in terms of neurological neglect-like symptoms. This 15 qualitative study sought to explore the nature of this phenomenon with a view to providing insights into central mechanisms and the 16 relationship with pain. Twenty-seven participants who met the IASP CRPS classification were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
246
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(267 citation statements)
references
References 25 publications
13
246
3
5
Order By: Relevance
“…Those with CRPS express a sense that the limb no longer belongs to them, referring to the limb in the third person and as foreign or alien (Forderreuther et al 2004;Galer et al 1995;Lewis et al 2007). Some describe hostile thoughts and feelings about the limb and report a strong desire for amputation despite receiving medical advice to the contrary (Lewis et al 2007).…”
Section: Disturbances In Body Perceptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Those with CRPS express a sense that the limb no longer belongs to them, referring to the limb in the third person and as foreign or alien (Forderreuther et al 2004;Galer et al 1995;Lewis et al 2007). Some describe hostile thoughts and feelings about the limb and report a strong desire for amputation despite receiving medical advice to the contrary (Lewis et al 2007).…”
Section: Disturbances In Body Perceptionmentioning
confidence: 99%
“…Some describe hostile thoughts and feelings about the limb and report a strong desire for amputation despite receiving medical advice to the contrary (Lewis et al 2007). Commonly, patients can easily identify the location at which they would like to remove the affected limb which is referred to clinically as the hypothetical amputation line.…”
Section: Disturbances In Body Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to pain provocation, we agree that this may reflect the enhanced sensitivity of the neural mechanisms underpinning pain. Another possibility is that a change in cardiovascular or respiratory function, both of which can be evoked by imagined exercise (8), causes the effect. Alternatively, McCabe et al have reported that patients with CRPS are vulnerable to situations that involve incongruence between motor commands and sensory feedback (6); perhaps that is the mechanism.…”
Section: To the Editorsmentioning
confidence: 99%